Penentu Minat Penggunaan QRIS Di Tempat Ibadah: Manfaat, Kemudahan, Risiko, dan Kepercayaan - Wardhani, Nisita; Indriyani, Yesika (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2026)
This study aims to analyze the determinants of interest in using QRIS in places of worship, namely perceived benefits, ease of use, risk, and trust. The phenomenon shows that students are interested in using QRIS for donations in places of worship. This study adopts a quantitative approach using primary data obtained through questionnaires distributed to students. The sampling method used non-probability sampling, while data analysis was performed using multiple linear regression with SPSS version 27. The results show that perceived benefits and ease of use do not significantly affect interest in using QRIS in places of worship. Conversely, perceived risk has a negative effect on interest in using QRIS in places of worship, meaning that the higher the perceived risk, the lower the interest in its use. Meanwhile, trust showed a significant positive effect on the interest in using QRIS in places of worship. These research results indicate that trust and risk perception are the main determinants of interest in using QRIS in places of worship, while perceived benefits and ease of use are not significant determinants.